Kegunaan Overmacht (Pemaksaan) dalam Pertanggungjawaban Tindak Pidana Korupsi yang Dilakukan Atas Perintah Jabatan di Indonesia - Rudy; Ariai; Abdul Jabar Rahim (Faculty of Law, Universitas Pekalongan, 2023)
This study aims to analyze the usefulness of the concept of overmacht (coercion) in the context of accountability for corruption crimes committed based on official orders. In law enforcement practice, there is often an excuse from corrupt perpetrators that their actions were carried out due to pressure from their positions or orders from superiors. This raises conceptual questions about the limits of individual responsibility and the existence of excuses for forgiveness in Indonesian criminal law. This research uses normative legal research methods with a statutory approach and a conceptual approach and is analyzed using a systematic and teleological interpretation of the provisions of Article 48 and Article 51 of the Criminal Code. The analysis is also associated with the principle of criminal accountability and the principle of substantive justice. The results of the study show that overmacht can only be used as a basis for eliminating wrongdoing if the pressure of position eliminates the freedom of the perpetrator's will. Bureaucratic pressure or institutional loyalty alone is not enough to justify corrupt acts. Thus, the application of overmacht in corruption cases must be carefully assessed by judges based on the context and intensity of office pressure. This study recommends the need to reformulate legal norms in the Corruption Law and strengthen education on office ethics, so that the concept of overmacht is not abused but still functions as an instrument of substantive justice in the Indonesian criminal law system.